2019
DOI: 10.1002/bies.201800239
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Pathogenicity of Congenital Zika and Guillain–Barré Syndromes: Does Dysregulation of RNA Editing Play a Role?

Abstract: Previous studies of Zika virus (ZIKV) pathogenesis have focused primarily on virus‐driven pathology and neurotoxicity, as well as host‐related changes in cell proliferation, autophagy, immunity, and uterine function. It is now hypothesized that ZIKV pathogenesis arises instead as an (unintended) consequence of host innate immunity, specifically, as the side effect of an otherwise well‐functioning machine. The hypothesis presented here suggests a new way of thinking about the role of host immune mechanisms in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 136 publications
(156 reference statements)
1
18
0
Order By: Relevance
“…In Latin America and the Caribbean, GBS incidence was estimated to have increased 2.6 times during the ZIKV outbreak [56]. It was hypothesized that ZIKV-GBS may be due to dysregulation of the activity of the RNA editing enzymes [57].…”
Section: Guillain-barré Syndrome and Emerging Infectious Diseasesmentioning
confidence: 99%
“…In Latin America and the Caribbean, GBS incidence was estimated to have increased 2.6 times during the ZIKV outbreak [56]. It was hypothesized that ZIKV-GBS may be due to dysregulation of the activity of the RNA editing enzymes [57].…”
Section: Guillain-barré Syndrome and Emerging Infectious Diseasesmentioning
confidence: 99%
“…In the CNS, dysregulation of IRE1 signaling is implicated in a number of neurodegenerative disorders [41]. It has been suggested that neuroinflammation following infection with neurotropic viruses may play a role in these mechanisms [42][43][44][45][46]. Our observation that IRE1 activation in astrocytoma cells was stronger for the neurotropic pathogenic TBEV strain Neudoerfl, suggests that immune-mediated pathomechanisms may contribute to the severe form of the disease that is not observed for the other two viruses.…”
Section: Discussionmentioning
confidence: 69%
“…5 b). Because ADARB1 and ADAR both share some overlapping editing targets as well as have gene-specific ones [ 52 , 53 ], this expression pattern suggests that both ADAR genes may play complementary roles in the differential response to ZIKV infection [ 54 ]. This would be consistent with prior suggestions that ADARB1 contributes to dysregulation of RNA editing in many diseases [ 55 58 ].…”
Section: Resultsmentioning
confidence: 99%